(untitled) (Journal of Philosophy Culture and Political Science, 2018)
This article discusses the issue related to the philosophy of Islam in Central Asia and Kazakhstan in the period of Karakhanids dynasty.You can see the subtle relationship between philosophy and theology of Islam that period, which were mainly in the ancient cities such as Samarkand, Isfijab, Turkistan. In this article, we reveal the topic of Islamic philosophy and philosophical – religious aspects of Muslim thought and its characteristics in Central Asia in the period Karakhanids dynasty. Islamic philosophy, especially the period dynasty is characterized by its merger with religion.Many philosophers and theologians were priests. In some cases, philosophers and theologians were higher than public office.In medieval religion of Islam – God – the absolute identity, God is one.A person is understood as the unity of faith, hope and love.Vitality, encased in Islam, is the development of personal principle.The man introduced himself in a new way, which in many respects superior to the ancient representations. Key words: fiqh (religionruls), Islam, philosophical ideas, theologians of the Muslim religion, the Medieval, the theory of Islamic thought.